Early hospital trainings in patients with left ventricular mechanical support: influence on exercise tolerance and muscle strength. (14th October 2021) - Smolis-Bak, E; Chwyczko, T; Zalucka, L; Noszczak, E; Bogucki, M; Segiet-Swiecicka, A; Piotrowicz, R; Dabrowski, R
Abstract: Background: In extreme cases of heart failure, the only method of treatment is heart transplantation. Due to the insufficient number of organs for transplantation, left ventricular assist devices (LVAD) are increasingly being used. Rehabilitation of patients with LVAD is a very important element of complex therapy due to the long-term immobilization of these patients awaiting transplant or regeneration of the heart. The aim of the study was to assess the impact of early hospital rehabilitation on exercise tolerance, muscle strength and complex coordination in patients after LVAD implantation. Material and methods: The study included 37 patients (35 men), aged 19–66 years, mean 58.7 years, after LVAD implantation. All of them underwent standard rehabilitation in the postoperative and rehabilitation department. The patients have started and continued trainings in a rehabilitation department for 4–5 weeks: endurance trainings, general fitness exercises with elements of balance and coordination exercises, elements of resistance exercises. Before the start of rehabilitation and after its completion, all patients underwent: cardiopulmonary exercise testing (CPET), a six-minute walk tests (6-MWT), the tests of strength of the right and left hand grip, strenght of muscles of the lower limbs and complex coordination (up and go test). There were no adverse events that would justify changing the mode or discontinuing rehabilitation. Results: A significant increase in the value of most of the parameters studied was observed after the completion of hospital rehabilitation: VO2peak [ml/kg/min], baseline: 10.60 (9.60, 12.90) vs. 12.85 (11.60, 15.73), p<0.001; 6-MWT [m]: 322.81 (113.62) vs. 416.12 (106.37), p<0.001; 30 second chair stand: no of stands: 9.12 (3.60) vs. 11.18 (4.50), p<0.001; up & go [sec] 9.18 (8.07, 10.50) vs. 7.58 (6.69, 9.04), p<0.001; left hand grip strengh [kg]: 30.04 (8.38) vs. 31.91 (8.10), p<0.011; right hand grip strengh [kg]: 31.52 (9.88) vs 33.20 (8.72), ns. Conclusions: Early hospital rehabilitation in patients after implantation of left ventricular assist devices has significant benefits in terms of exercise tolerance, muscular strength and complex coordination. Complex rehabilitation is safe and effective in this group of patients. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): STRATEGMED II - RH-ROT - NATIONAL RESEARCH AND DEVELOPMENT CENTER